An Analysis of "Literasi Bahasa Inggris" Difficulties in "Seleksi Nasional Berbasis Tes" (SNBT) by Senior High School Students at SMAS Harapan 3 Deli Tua - Yunanda, Fachri; Husda, Azizah (English Teaching and Linguistics Journal (ETLiJ), 2025)
A number of studies on Literasi Bahasa Inggris in SNBT have been extensively researched in educational communication; however, few studies have investigated the challenges of Literasi Bahasa Inggris queries among secondary school students. This study was conducted to determine the difficulties that high school students faced when answering Literasi Bahasa Inggris questions on the SNBT test. The method employed in this research is qualitative method. This study focused on high school pupils who had taken the SNBT test. According to the findings of this study, the most significant issue in the Literasi Bahasa Inggris test was a lack of vocabulary, which led to frustration when they saw vocabulary-related questions, and it was still difficult for them to answer questions about assumptions and hypotheses in the text due to a lack of logical thinking. They also believed that the time allotted to answer the questions was insufficient. So, according to the research, in order to overcome these difficulties, high school students must improve their vocabulary mastery related to Literasi Bahasa Inggris questions both at home and at school, as well as their logical thinking and ability to manage time so that it is easier to work on problems in the Literasi Bahasa Inggris section